Diet as connecting factor: Functional brain connectivity in relation to food intake and sucrose tasting, assessed with resting‐state functional MRI in rats. Issue 5 (26th November 2019) - Roelofs, Theresia J. M.; Straathof, Milou; van der Toorn, Annette; Otte, Willem M.; Adan, Roger A. H.; Dijkhuizen, Rick M.
Abstract: Eating disorders and obesity form a major health problem in Western Society. To be able to provide adequate treatment and prevention, it is necessary to understand the neural mechanisms underlying the development of eating disorders and obesity. Specific brain networks have been shown to be involved in feeding behavior. We therefore hypothesized that functional connectivity in neural networks involved in feeding behavior is dependent on the status of homeostatic energy balance, thus on being hungry or satiated. To test our hypothesis, we measured functional connectivity and amplitudes of neural signals within neural networks in relation to food intake and sucrose tasting in rats. Therefore, 16 male Wistar rats, of which eight were food‐restricted and eight were satiated, underwent resting‐state functional magnetic resonance imaging (rs‐fMRI) at 9.4 T. Subsequently, half of these animals underwent a sucrose tasting procedure followed by a second rs‐fMRI scan. Functional connectivity and amplitude of low‐frequency signal fluctuations were statistically analyzed in a linear mixed model. Although we did not detect a significant effect of food intake on functional connectivity before sucrose tasting, there was a trend toward interaction between group (satiated vs. hungry) and treatment (sucrose tasting). Functional connectivity between feeding‐related regions tended to decrease stronger upon sucrose tasting in satiated rats as compared to food‐restricted rats. Furthermore, rs‐fMRI signal amplitudes decreased stronger upon sucrose tasting in satiated rats, as compared to food‐restricted rats. These findings indicate that food intake and sucrose tasting can affect functional network organization, which may explain the specific patterns in feeding behavior. Abstract : Food intake and sucrose tasting can affect functional network organization, as measured with resting‐state functional MRI in satiated and food‐restricted rats.